Optimalisasi Komunitas Belajar bagi Guru di SMA Muhammadiyah 1 Jombang - Kantrey Sugiarto; R. Kurniawan Bagus Wicaksono; Wahyuni Aslamiyah; Rivana Fitri Ramadhani; Mayong Gagat Satrio Wredanadi; Defiania Cindy Adi Putri; Rochmi Jihad Fatihah (Universitas Nurul Jadid, 2024)
In the 2022/2023 academic year, SMA Muhammadiyah 1 Jombang implemented the Merdeka Curriculum, initially applied to Class X students, and extended to Classes X and XI in the 2022/2024 academic year. To successfully achieve the outcomes of this curriculum, optimizing the Learning Community within the school is essential. Despite the involvement of partners in various efforts to strengthen the Learning Community as a Driving School, there have been challenges in fully optimizing it in line with government guidelines. This community service program, conducted by the Faculty of Law, Soerjo University, aims to assist teachers in designing, implementing, and reflecting on Learning Communities that align with the Learning Community Optimization Guidelines. The approach utilized includes socialization activities, training, technology application, mentoring, and ensuring program sustainability. As a result of this initiative, teachers have gained the ability to design, implement, and reflect on Learning Communities according to the prescribed guidelines. Furthermore, the program has helped establish teacher habits focused on student-centered learning, fostering cooperation among educators, and promoting shared responsibility, all while referring to student learning outcome data. These outcomes have led to positive changes in the learning environment facilitated by the partners